G395 Evaluation of the small wonders change programme. (27th April 2016) - Yoxall, CW; Niccol, C; Baum, A; Watt, T; Wood, E; Dykes, F; Crossland, N; Thomson, G; Wallace, L; Grunfeld, B; Whiteman, B; Kwah, K; et al.
Abstract : Aims: The Small Wonders Change Programme (SWCP) is a complex intervention designed by the charity Best Beginnings to improve family-centred practices in neonatal care. The main component of SWCP is a series of films on a DVD supported by a staff training package. The aim of this study was to evaluate the impact of SWCP on staff knowledge and attitudes, parental knowledge and experience and preterm feeding outcomes. Methods: A mixed methods evaluation was performed in two NICUs. Measurements made on cohorts of staff, parents and babies recruited in a period before the intervention (pre) and after the intervention had been embedded (post) were compared. Results: Staff – Knowledge and confidence were assessed in 182 (pre) and 63 (post) staff. Knowledge scores increased from a mean (SD) of 25.71 (3.74) to 28.65 (2.95), p < 0.001. Confidence scores increased from a mean (SD) of 63.93 (13.01) to 74.70 (9.37), p < 0.001. Qualitative analysis of semi-structured interviews revealed that clinicians valued the evidence-based programme and were motivated to integrate their knowledge into practice Parents – 110 (pre) and 64 (post) parents were surveyed. There were several significant improvements in relation to information received, infant feeding intentions and practices (Table 1 ). 85.7% of mothers had received a DVD. Only 45.2% watched it. 78.9% of those rated it as either 'very helpful' or 'helpful'. All fathers rated it as either 'helpful' or 'very helpful'. Clinical outcomes – Clinical outcomes of 617 (pre) and 590 (post) preterm babies were compared. The proportion of babies receiving breast milk at discharge increased from 42.4% to 49% (p = 0.02). The days on which breast milk was used as a proportion of days on which any enteral feeding occurred increased from 57.2% to 62.8% (p < 0.0001). There were no differences in any other clinical outcome. Conclusions: SWCP improved staff knowledge and confidence in supporting preterm breast feeding and family centred care, parental experience and the amount of breast milk received by preterm babies.